2013
DOI: 10.1002/hep.26237
|View full text |Cite
|
Sign up to set email alerts
|

Efficient drug screening and gene correction for treating liver disease using patient-specific stem cells

Abstract: Patient-specific induced pluripotent stem cells (iPSCs) represent a potential source for developing novel drugand cell- therapies. Although increasing numbers of disease-specific iPSCs have been generated, there has been limited progress in iPSC-based drug screening/discovery for liver diseases, and the low gene targeting efficiency in human iPSCs warrants further improvement. Using iPSC lines from patients with alpha-1 antitrypsin (AAT) deficiency, for which there is currently no drug- or gene- therapy availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
194
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(202 citation statements)
references
References 50 publications
2
194
1
1
Order By: Relevance
“…While iPSCs have been used to model a number of human diseases (Yagi et al 2011;Choi et al 2013;Liang et al 2013;Miller et al 2013;Aflaki et al 2014;Pashos et al 2017;Cayo et al 2017), there is a limited amount of work demonstrating their ability to model regulatory phenotypes Alasoo et al 2017). iPSC-CMs recapitulate gene expression patterns observed in primary heart tissue obtained from the GTEx Consortium, and eQTLs identified in iPSC-CMs are also enriched among eQTLs identified in primary heart tissue (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While iPSCs have been used to model a number of human diseases (Yagi et al 2011;Choi et al 2013;Liang et al 2013;Miller et al 2013;Aflaki et al 2014;Pashos et al 2017;Cayo et al 2017), there is a limited amount of work demonstrating their ability to model regulatory phenotypes Alasoo et al 2017). iPSC-CMs recapitulate gene expression patterns observed in primary heart tissue obtained from the GTEx Consortium, and eQTLs identified in iPSC-CMs are also enriched among eQTLs identified in primary heart tissue (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic Differentiation-Human iPSCs were differentiated into hepatocytes using protocols previously reported (30,31), with some modifications. The overall procedures are described in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…TALENs have been used to correct a mutation found in patients suffering from alpha-1 antitrypsin (AAT) deficiency, a genetic liver disorder that predisposes patients to liver cirrhosis and hepatocellular carcinoma, cystic fibrosis, and Gaucher's disease. 72,73 Moreover, CRISPR/Cas9 has been used to study cystic fibrosis by correcting a mutation found in the transmembrane conductor receptor (CFTR) gene in primary adult stem cells. 74 TALENs and the CRISPR/Cas9 system have also been used to target mutations found in iPS cells derived from Duchenne muscular dystrophy (DMD) patients.…”
Section: -37mentioning
confidence: 99%